Automated formative assessments are associated to successful academic outcomes among first year anatomy students - De Oliveira, Beatriz Ito Ramos; Ng, Leo; Furness, Anne; Owens, John; Jacques, Angela; Travers, Mervyn (2019)
Introduction: Formative assessments can be useful in motivating student academic success through feedback and can be particularly helpful for first year anatomy students. However, this is often precluded by large student numbers. In order to enable formative assessments to large student numbers, an automated assessment system was utilised. The main aims were to assess if automated formative scores were associated to improved summative scores and if they could ultimately be used to predict academic outcomes among first year anatomy students. Material and Methods: A quasi-experimental study assessed 220 students enrolled in an anatomy course over six time points: formative assessments 1 (FAx 1) and 2 (FAx2) before the Mid-semester summative assessment, and formative assessments 3 (FAx 3) and 4 (FAx4) before the Final summative assessment. Linear models were used to assess if formative scores were associated with summative scores to predict academic outcomes. Results: Mean Mid-semester scores (x ̅=60.28%) improved by 28.73% and 21% compared to FAx1 (x ̅=31.55%) and FAx2 (x ̅= 39.28). FAx1 and FAx2 scores were moderately-to-strongly correlated with Mid-semester scores (FAx1: r= 0.710, p<0.001; FAx2: 0.682, p<0.001). Mean Final scores (x ̅=70.32%) also improved by 34.03% and 30.03% compared to FAx3 (x ̅=36.29%) and FAx4 (x ̅=39.47%). FAx3 and FAx4 were also moderately-to-strongly correlated to Final scores (FAx3: r= 0.706, p<0.001; FAx4: r= 0.719, p<0.001). Conclusion: Students performed progressively better on automated formative assessments in the lead-up to automated summative assessments and formative scores can be used to predict academic outcomes among a large number of first year anatomy students.